2021
DOI: 10.3390/jpm11101011
|View full text |Cite
|
Sign up to set email alerts
|

Using Cone-Beam Computed Tomography to Assess Changes in Alveolar Bone Width around Dental Implants at Native and Reconstructed Bone Sites: A Retrospective Cohort Study

Abstract: The aim of this study was to use a cone-beam computed tomography (CBCT) to assess changes in alveolar bone width around dental implants at native and reconstructed bone sites before and after implant surgery. A total of 99 implant sites from 54 patients with at least two CBCT scans before and after implant surgery during 2010–2019 were assessed in this study. Demographic data, dental treatments and CBCT scans were collected. Horizontal alveolar bone widths around implants at three levels (subcrestal width 1 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Regarding the bone width changes, there was a decrease in CBW, MBW and ABW after 6 months which was significant for the MBW (9.32 mm and 8.72 mm immediate postoperative and after 6 months respectively) where the mean width decreased by 0.6mm. This was consistent with Hu et al (31) where the middle part of the ridge underwent a significant resorption (0.39 ± 1.12 mm), measured using CBCT scans, at both native and reconstructed bones before and after implant surgery. After ridge augmentation, the augmented bone particles undergo resorption and remodeling, together with the blood clot, the fibrin glue, and the soft tissue pressure all contribute to the reduction in the graft width.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the bone width changes, there was a decrease in CBW, MBW and ABW after 6 months which was significant for the MBW (9.32 mm and 8.72 mm immediate postoperative and after 6 months respectively) where the mean width decreased by 0.6mm. This was consistent with Hu et al (31) where the middle part of the ridge underwent a significant resorption (0.39 ± 1.12 mm), measured using CBCT scans, at both native and reconstructed bones before and after implant surgery. After ridge augmentation, the augmented bone particles undergo resorption and remodeling, together with the blood clot, the fibrin glue, and the soft tissue pressure all contribute to the reduction in the graft width.…”
Section: Discussionsupporting
confidence: 91%
“…35 Our previous study demonstrated significant alveolar bone width resorption at CW4 level and no significant difference between the maxilla and mandible. 12 Most studies have indicated that the alveolar bone's thickness decreases after implant surgery. 36,37 The finding of the present study that alveolar bone width increased at CW1 after implant surgery has not been reported by any other study.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Some studies have used the multiplanar reformatted mode in cone-beam computed tomography (CBCT) to examine the alveolar bone. 12,13 Other studies have employed nearby anatomical landmarks to determine the position and angle of the measurement plane. [14][15][16] However, implant surgery with sinus lift or ridge augmentation can cause obvious changes in the surrounding tissue, which can affect the measurement's accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Endosseous implant was selected for replacing the missing teeth as it better preserved the alveolar bone when compared to a fixed prosthesis [20][21][22][23] . The maxillary lateral incisors were built up using dental composites to improve aesthetics.…”
Section: Discussionmentioning
confidence: 99%